IMPLEMENTASI WEB-BASED TRANSPORTATION MANAGEMENT SYSTEM DI INDUSTRI TRANSPORTASI : SYSTEMATIC LITERATURE REVIEW - Alyah Nur Alifah; Elsa Elsa; Muh. Taufiq Ahmadi; Riksal Rivaldi; Dhimas Tribuana (Plexi Digital Indonesia, 2025)
This systematic literature review examines 20 publications from 2020 to 2025 addressing the implementation of web-based Transportation Management Systems (TMS) across various transport sectors. Our analysis identifies three major clusters: first, enhanced operational visibility and fleet tracking via web/cloud solutions; second, process optimization through system integration, automation, and log-based analytics; third, significant implementation challenges stemming from organizational readiness, legacy system integration, and web security concerns. The three clusters interact with each other, so the success of web-based TMS depends not only on technology, but also on human involvement, processes, and infrastructure. From a theoretical perspective, our findings suggest extending technology adoption frameworks (e.g., TOE) to include variables such as data interoperability, digital readiness, and data governance. In practical terms, companies should conduct a comprehensive data readiness assessment, plan system integration (such as API or ERP), manage organizational change, and implement robust web security before launching a web-based transportation management system (TMS). Additionally, implementing real-time analytics and process mining on TMS logs is essential for continuous improvement. This review is limited by the heterogeneity of publication types (academic journals, industry reports, implementation projects), the lack of long-term quantitative performance data, and the absence of cross-country comparative studies. Future research should pursue multi-industry longitudinal studies, systematically evaluate web-based TMS performance metrics, and investigate security and interoperability issues as core components of the modern digital transportation ecosystem.